2017
DOI: 10.1159/000455113
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Online Resources to Prioritize Candidate Genes for Functional Analyses: Using the Fetal Testis as a Test Case

Abstract: With each new microarray or RNA-seq experiment, massive quantities of transcriptomic information are generated with the purpose to produce a list of candidate genes for functional analyses. Yet an effective strategy remains elusive to prioritize the genes on these candidate lists. In this review, we outline a prioritizing strategy by taking a step back from the bench and leveraging the rich range of public databases. This in silico approach provides an economical, less biased, and more effective solution. We d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 73 publications
(123 reference statements)
0
4
0
Order By: Relevance
“…Online databases containing sequencing and functional data have improved dramatically over the last decade, and such 'in silico' resources greatly aid identification of the causal variant and biological interpretation of findings from GWAS discovery efforts. 27,91 For instance, the ongoing accrual of data on coding variants (via exome sequencing and/or exome array genotyping) has been extremely useful in assigning correct causal coding variants to GWAS peaks. 92,93 Additionally, given that GWAS findings have largely implicated non-coding variation, sequence annotation of tissue-specific chromatin states and protein binding (e.g.…”
Section: New In Silico and Genomic Approaches To Understanding Osamentioning
confidence: 99%
“…Online databases containing sequencing and functional data have improved dramatically over the last decade, and such 'in silico' resources greatly aid identification of the causal variant and biological interpretation of findings from GWAS discovery efforts. 27,91 For instance, the ongoing accrual of data on coding variants (via exome sequencing and/or exome array genotyping) has been extremely useful in assigning correct causal coding variants to GWAS peaks. 92,93 Additionally, given that GWAS findings have largely implicated non-coding variation, sequence annotation of tissue-specific chromatin states and protein binding (e.g.…”
Section: New In Silico and Genomic Approaches To Understanding Osamentioning
confidence: 99%
“…FOXO4 has been implicated as a negative regulator of cell proliferation in several tumours, but a link to steroidogenesis has not previously been established ( Li et al , 2016 ). GRAMD1B has been shown to be enriched in mouse fetal Leydig cells following CRHR1 agonist stimulation ( McDowell et al , 2012 ), and has been identified in other expression studies of mouse fetal Leydig cells ( Inoue et al , 2016 ; McClelland & Yao, 2017 ). We have shown by immunohistochemistry that there is clear upregulation of GRAMD1B in the cytoplasm of NR5A1-positive steroidogenic cells with the onset of steroidogenesis in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Adrenal development and gonad development are two of the most fundamental biological processes. However, current knowledge about the genetic mechanisms underlying these events is derived largely from studies in mice ( Beverdam & Koopman, 2006 ; Inoue et al , 2016 ; Jameson et al , 2012 ; McClelland et al , 2015 ; McClelland & Yao, 2017 ; McDowell et al , 2012 ; Nef et al , 2005 ; Xing et al , 2015 ) and few data are currently available from humans ( Fowler et al , 2009 ; Gerrard et al , 2016 ; Houmard et al , 2009 ; O’Shaughnessy et al , 2007 ), especially during the first trimester or across all three tissues. Of the published data, the recent study from Gerrard et al .…”
Section: Discussionmentioning
confidence: 99%
“…Adrenal development and gonad development are two of the most fundamental biological processes. However, current knowledge about the genetic mechanisms underlying these events is derived largely from studies in mice (Beverdam & Koopman, 2006; Inoue et al, 2016; Jameson et al, 2012; McClelland et al, 2015; McClelland & Yao, 2017; McDowell et al, 2012; Nef et al, 2005; Xing et al, 2015) and few data are currently available from humans (Fowler et al, 2009; Gerrard et al, 2016; Houmard et al, 2009; O’Shaughnessy et al, 2007), especially during the first trimester or across all three tissues. Of the published data, the recent study from Gerrard et al .…”
Section: Discussionmentioning
confidence: 99%